Výpravy do země jiných vad. Český (ne)romantizmus očima polských publicistů - Pešina, Jan (Wydawnictwo Rys (nr 1), 2011)
One of so called “proprietes of a national characte“, which in Poland is sometimes stereotypically attributed to the Czechs, is a realistic or even pragmatic outlook on life, opposite to a Polish national romantic philosophy. This essay is devoted to the problem of the above mentioned romantism and realism as the way of thinking/mental state. On the base of Polish books published in the previous decade, dedicated to the modern Czech history, society and the wide understood culture, we have tried to answer the question, if and how Polish authors address the above mentioned stereotypical perception of the southern neighbour. It was displayed, that the most of the investigated authors, by choosing unique, romantic subjects and ideas, try to suppress the Polish stereotypical images of the Czechs.
The expeditions to the land of other flaws. Czech (non)Romantism in the eyes of Polish publicists
Keywords: Czech; Romanticism; Publicity; Stereotype; National character